Implications on RC structure performance of model parameter sensitivity: Effect of chlorides - Ferreira, Rui Miguel (Journal of Civil Engineering and Management, 2010)
This paper presents a sensitivity analysis of the parameters of the model presented in the fib – Model Code for Service Life Design for corrosion initiation due to chloride penetration. In order to adequately apply probabilistic models, a basic understanding of the model and the parameters used and the impact input values for the model parameters have on the outcome is necessary. An erroneous parameter value selection has consequences that are not always appreciated. A sensitivity analysis of the main model parameters was performed by analysing the presented model outcome. The parameter's average value was varied in a range of 20% with respect to the reference average value, whereas keeping the standard deviation constant. The results of the sensitivity analysis show that the reinforcement concrete cover and the ageing exponent of the chloride migration coefficient parameters are those that most influence the outcome of the model and therefore the durability performance of the concrete structure. The least influential model parameters, contrary to what might be expected, are Ccrit and C S,Δx. Furthermore, the importance of environmental temperature on the outcome is noted. The choice of model parameter value is a critical one. Due to the uncertainty of current knowledge with regard to certain parameters caution should be exercised in the use of these models.First Published Online: 10 Feb 2011